Ted Honderich on Consciousness, Determinism, and Humanity (Philosophers in Depth, 2018)
This fascinating collection assembles leading philosophers of mind, metaphysics and morals to examine the impact of the work of Ted Honderich, Grote Professor Emeritus of the Philosophy of Mind and Logic at University College London, UK. The insightful analyses are accompanied by replies from Ted Honderich himself, providing the most comprehensive critical treatment of his accomplishments to date. The essays focus on three major areas of Honderich's work: his theory of actual consciousness; his extensive and ground-breaking work on determinism and freedom; and his views on right and wrong, including his Principle of Humanity and his writings on terrorism. This volume is essential reading for all scholars interested in the work of Ted Honderich, and in the debates surrounding the philosophy of mind, metaphysics, free will and moral responsibility, and social and political philosophy.